Neural Correlates of Vestibular Processing During a Spaceflight Analog With Elevated Carbon Dioxide (CO2): A Pilot Study - Hupfeld, Kathleen E.; Lee, Jessica K.; Gadd, Nichole E.; Kofman, Igor S.; De Dios, Yiri E.; Bloomberg, Jacob J.; Mulavara, Ajitkumar P.; Seidler, Rachael D. (Frontiers in Systems Neuroscience, 2020)
Astronauts return to Earth from spaceflight missions with impaired mobility and balance; recovery can last weeks postflight. This is due in large part to the altered vestibular signaling and sensory reweighting that occurs in microgravity. The neural mechanisms of spaceflight-induced vestibular changes are not well understood. Head-down-tilt bed rest (HDBR) is a common spaceflight analog environment that allows for study of body unloading, fluid shifts, and other consequences of spaceflight. Subjects in this context still show vestibular changes despite being in Earth’s gravitational environment, potentially due to sensory reweighting. Previously, we found evidence of sensory reweighting and reduced neural efficiency for vestibular processing in subjects who underwent a 70-day HDBR intervention. Here we extend this work by evaluating the impact of HDBR paired with elevated carbon dioxide (CO2) to mimic International Space Station conditions on vestibular neural processing. Eleven participants (6 males, 34 ± 8 years) completed 30 days of HDBR combined with 0.5% atmospheric CO2 (HDBR+CO2). Participants underwent six functional magnetic resonance imaging (fMRI) sessions pre-, during, and post- HDBR+CO2 while we measured brain activity in response to pneumatic skull taps (a validated method of vestibular stimulation). We also measured mobility and balance performance several times before and after the intervention. We found support for adaptive neural changes within the vestibular system during bed rest that subsequently recovered in several cortical and cerebellar regions. Further, there were multiple brain regions where greater pre- to post- deactivation was associated with reduced pre- to post- balance declines. We also found that, compared to HDBR alone (n = 13 males; 29 ± 3 years) HDBR+CO2 is associated with greater increases in activation of multiple frontal, parietal, and temporal regions during vestibular stimulation. This suggests interactive or additive effects of bed rest and elevated CO2. Finally, we found stronger correlations between pre- to post- HDBR+CO2 brain changes and dependence on the visual system during balance for subjects who developed signs of Spaceflight-Associated Neuro-ocular Syndrome (SANS). Together, these findings have clear implications for understanding the neural mechanisms of bed rest and spaceflight-related changes in vestibular processing, as well as adaptation to altered sensory inputs.